Analisis Dampak Penerapan PSAK 73 Tentang Sewa Pada Kinerja Keuangan Industri Pertambangan di Tahun 2024 - Verawati Verawati; Linda Santioso (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of the implementation of the Indonesian Financial Accounting Standard (PSAK) No. 73 on Leases on the financial performance of the mining industry in Indonesia in 2024. PSAK 73, which adopts IFRS 16, changes the accounting treatment of leases by requiring the recognition of Right-of-Use Assets and Lease Liabilities in the statement of financial position. The research employs a descriptive quantitative approach with a comparative design, using secondary data from financial reports of mining companies listed on the Indonesia Stock Exchange (IDX). The results show that the adoption of PSAK 73 increases the average Debt-to-Asset Ratio (DAR) from 39.15% to 39.92% and the Debt-to-Equity Ratio (DER) from 72.21% to 74.60%. These increases indicate higher leverage due to lease capitalization without changes in equity. The greatest impact is observed in PT Bukit Asam Tbk, while the smallest in PT Antam Tbk. Overall, the implementation of PSAK 73 leads to a technical increase in financial leverage, implying the need for careful liability management and transparent communication with investors to mitigate potential negative perceptions of company performance.